The Impact of Feedback in Improving Students' Descriptive Writing Skills: A Case Study at SMPN 1 Hu’u - Nurilah, Nurilah; Syarifuddin, Syarifuddin; Suciwati, Ika (Journal of Educational Sciences, 2025)
This study aims to determine the significant influence of giving feedback on improving the descriptive writing ability of grade VIII students at SMP Negeri 1 Hu'u, Dompu, Indonesia. This study used a quantitative method with an experimental design of 20 students who were divided into experimental and control groups. In this study, the results of the pre-test showed that 65% of students obtained scores below 70. After providing feedback, the percentage of students who scored above 70 increased to 85%. To calculate the student score data, the researchers used a paired sample t-test that showed a significant improvement (p = 0.001) with a correlation value of 0.662. An analysis of the effect size yielded a Cohen value d = -1.602, indicating a large effect of the intervention. In addition, questionnaire data showed that more than 80% of students responded positively to feedback, and observations showed an improvement in students' understanding of the structure and language features of descriptive texts.